2014
DOI: 10.1080/19443994.2014.908147
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr(VI) from aqueous solution on seeds ofArtimisia absinthium(novel plant material)

Abstract: A B S T R A C TArtimisia absinthium, a medicinal plant material, showed excellent adsorption in removing mutagenic Cr(VI) from aqueous solution along with Cu(II), Ni(II), and Zn(II). Various parameters like effect of pH, contact time, temperature, and initial concentration were investigated using batch process to optimize conditions for maximum adsorption. A. absinthium was characterized using scanning electron microscopy (SEM). Adsorption of Cr(VI) was favorable at pH 2 as 96% of Cr(VI) could be removed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Procedures such as technologies of membrane filtration, reverse osmosis chemical precipitation, ion exchange, evaporation, solvent extraction, ion exchange and electrochemical treatment, have been employed severally to eliminate these harmful toxins from wastewater. Because of the inability of these methods to adsorb metals with low concentration, the use of adsorption has been employed which has proven to be effective and efficient because of its reduced cost and ease of handling [5, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Procedures such as technologies of membrane filtration, reverse osmosis chemical precipitation, ion exchange, evaporation, solvent extraction, ion exchange and electrochemical treatment, have been employed severally to eliminate these harmful toxins from wastewater. Because of the inability of these methods to adsorb metals with low concentration, the use of adsorption has been employed which has proven to be effective and efficient because of its reduced cost and ease of handling [5, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…al. [103] and results showed higher removal efficeincy and Artimisa proved as a novel plant material for cadium removal. Unuabonah et al [120] performed the experiment on polyvinyl alcohol modified kaolinite clay for the removal of Pb(II) from water and concluded that modified natural clay (kaolinite) as a good adsorbent for removal of Pb(II).…”
Section: Discussionmentioning
confidence: 94%
“…Several methods for Cd 2+ ions removal from water/wastewater have been investigated over the last several decades, including chemical precipitation [ 11 ], membrane separation [ 12 ], ion exchange [ 13 ], and adsorption [ 7 , 14 , 15 ]. Amongst these techniques, adsorption has emerged to be the most promising treatment technology because of its high removal efficiency, low cost and ease of operation [ [16] , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%